Conflicting Effects of Methylglyoxal and Potential Significance of miRNAs for Seizure Treatment - Tao, Hua; Zhou, Xu; Zhao, Bin; Li, Keshen (Frontiers in Molecular Neuroscience, 2018)
According to an update from the World Health Organization, approximately 50 million people worldwide suffer from epilepsy, and nearly one-third of these individuals are resistant to the currently available antiepileptic drugs, which has resulted in an insistent pursuit of novel strategies for seizure treatment. Recently, methylglyoxal (MG) was demonstrated to serve as a partial agonist of the gamma-aminobutyric acid type A (GABAA) receptor and to play an inhibitory role in epileptic activities. However, MG is also a substrate in the generation of advanced glycation end products (AGEs) that function by activating the receptor of AGEs (RAGE). The AGE/RAGE axis is responsible for the transduction of inflammatory cascades and appears to be an adverse pathway in epilepsy. This study systematically reviewed the significance of GABAergic MG, glyoxalase I (GLO1; responsible for enzymatic catalysis of MG cleavage) and downstream RAGE signaling in epilepsy. This work also discussed the potential of miRNAs that target multiple mRNAs and introduced a preliminary scheme for screening and validating miRNA candidates with the goal of reconciling the conflicting effects of MG for the future development of seizure treatments.